2018
DOI: 10.21273/hortsci13541-18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating On-demand Irrigation Systems for Container-grown Woody Plants Grown in Biochar-amended Pine Bark

Abstract: Additional index words. automatic irrigation system, nursery crops, overhead irrigation, plantbased irrigation, substrate-based irrigation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…This study showed that plant available water potential can be different in different substrates and it can extend beyond −10 kPa tension for some substrates. Other recent studies also reported a dynamic range of plant available water depending on substrate type, or plant species [13,27,28] and an extended range of plant available water potential [13,29]. Our results showed that species-specific plant available water and water buffering capacity determination in the greenhouse using plant gas exchange parameters are a more accurate approach than the laboratory-based tests that consider −10 kPa tension as the end range of water buffering capacity.…”
Section: Photosynthetic Ratesupporting
confidence: 67%
See 3 more Smart Citations
“…This study showed that plant available water potential can be different in different substrates and it can extend beyond −10 kPa tension for some substrates. Other recent studies also reported a dynamic range of plant available water depending on substrate type, or plant species [13,27,28] and an extended range of plant available water potential [13,29]. Our results showed that species-specific plant available water and water buffering capacity determination in the greenhouse using plant gas exchange parameters are a more accurate approach than the laboratory-based tests that consider −10 kPa tension as the end range of water buffering capacity.…”
Section: Photosynthetic Ratesupporting
confidence: 67%
“…The models' r 2 are provided in the last column of the table. = a/(1 + exp (−(VWC − x 0 ) The sigmoidal relationship between VWC and plant gas exchange, specifically the maximum or near maximum gas exchange rate over a range of moisture levels, was consistent with that of 'Silver Dollar' hydrangea and hibiscus 'Cashmere Wind' grown in substrates containing pine bark, peat moss, and/or biochar [25,27,36]. Coir treatments supported a higher maximum predicted photosynthetic rate in comparison to the non-amended pine bark.…”
Section: Plant Gas Exchange Parametersmentioning
confidence: 53%
See 2 more Smart Citations
“…As shown in Figure 5, the dramatic change in moisture content is noticeable in traditional systems under standard irrigation practices. The irrigation schedule implemented in container production (N. Jahromi et al., 2018) paired with the manipulation of the hydraulic characteristics of a substrate profile (Fields, Owen, & Altland, 2021) can have a strong effect on substrate moisture status within substrate systems (Criscione et al., 2021). Cyclic irrigation applications can increase (less negative) Ψ upper values by continuously replacing water lost through either surface evaporation or downward through gravitational pull (Figure 5B).…”
Section: Discussionmentioning
confidence: 99%